"Global Africa": A Critical Genealogy of a Militant Concept - (:unkn) unknown (My University, 2022)
While the term Global Africa seems to be increasingly used in sectors as diverse as art, fashion, banking, services and academic research to evoke the multiple connections between Africa and the world, it is worth returning to the activist origins of this term. Indeed, the term stems directly from African and international activism of the early 1990s, which claimed the right to reparations for slavery and colonialism. One step further, the term can be almost superimposed on the social and political history of Pan-Africanism over several centuries and across spaces. The author adopts a pedagogical approach that presents two salient works on the subject (by A. Mazrui and M. O. West) and mobilizes a multilingual and multidisciplinary bibliography to analyse the term in order to clarify the project and the struggles underpinning its use. The article covers the critical origins of Global Africa from its militant emergence to its institutionalization by the African Union and UNESCO. It argues that the stakes are high and the key issue is to grasp the changes in the way we think and represent Africa and Africans in our globalised world.
Keywords: African Research